Composição nutricional de residuos de frutas com uso potencial na alimentação de aves - Mesquita, Ana Cecília Nunes de (2018)
Alternative foods have become a reality in the feeding of monogastric animals, for example, tropical residues and by-products to birds of zootechnical interest, in an attempt to reduce production costs. The knowledge of the nutritional composition necessary to possibly be used as ingredients in the diets with the purpose of providing some nutritional benefit, exemplified by the quality of the fiber, also generating environmental benefits. The objective of this work was to analyze the bromatological composition, especially the fibrous fraction, and some bioactive compounds present in fruit residues and by-products usable in animal feed. The physicochemical analyzes were performed on the selected samples of bark, bagasse and / or seeds of pineapple, acerola, cashew, guava, graviola, papaya, passion fruit and melon, with emphasis on mineral matter (MM), crude protein PB), ethereal extract (EE), and cell wall fractionation in soluble compounds of the hemicellulose type (neutral detergent fiber - NDF) and insoluble (acid detergent fiber - FDA), lignins (LIG), pectins (PEC) and bioactive substances type carotenoids (β-carotene and lycopene). The results of the analyzes showed that the values of MM were higher in residues composed of shell and passion fruit seeds (5.09%) followed by pineapple bark (3.92%), fibers and phytates present in fruit residues, have strong ionic bonding ability with mineral elements being able to decrease their absorption and bioavailability. PB were higher in the residues composed of melon bark (16.71%), papaya peels (14.10%) and graviola peels and seeds, these nitrogenous compounds are bound to the cell wall because the association between lignin and protein is a factor inherent to the constitution of the plant. EE were higher in graviola residues (23.23%), followed by residues composed of shells and passion fruit seeds (12.85%), since these residues were seeds. Hemicellulose (FDN-FDA) were higher in passion fruit (18.22%) and pineapple (16.24%) residues, due to the greater presence of arabinoxylans in the inner shells. The pulp contents (FDA-LIG) were higher in passion fruit residues (31.47%), a material constituted by bark and whereas in guava (30.60%) with higher quantity of seeds (lignified fibers). It was observed in the residues of melon (8.69%) and passion fruit (7.36%) higher concentrations of pectin because this nutrient is in the albedo located in the inner part of the bark. The papaya residue had the highest levels of ß-carotene and lycopene among the residues studied (0.27 mg / g and 0.48 mg / g). The residues of papaya, melon, cashew and guava are distinguished by the concentration of PB above 10%, among them, papaya, melon and cashew, in order of increasing size, they have the best fibrous composition, presenting the lowest values of NDF, FDA and lignin. Taking into account the bioactive compounds and bromatological composition analyzed the residue of the papaya is the one with the greatest potential of use in the feeding of chickens